Market Intelligence MELIA workshop - Saakova, Svetlana; Carampatana, Jake; Bonaiuti, Enrico; Polar, Vivian; Demont, Matty; Belcher, Brian (2023)
The Market Intelligence initiative organized a MELIA workshop during its first year of implementation. The workshop objectives were: a) Building a shared vision on the Initiative across the team; b) Ensuring alignment with other Genetic Innovation Initiatives; c) Providing Market Intelligence team with a solid framework for Planning and Reporting for this year and the next ones. The workshop was conducted in Nairobi and 60 participants attended.